With or without you: associations between frequency of internet pornography use and sexual relationship outcomes for (non)consensual (non)monogamous individuals - Rodrigues, D. L.; Lopes, D.; Dawson, K.; Visser, R.; Štulhofer, A. (Archives of Sexual Behavior, 2021)
More frequent internet pornography use is often associated with decreased sexual satisfaction. However, individuals who use internet pornography more often can experience better relationship outcomes, depending on how they use it in the context of their relationship. Indeed, internet pornography use with the partner seems to be positively associated with sexual satisfaction. We explored whether the type of agreement partners have about monogamy is related to this association. We conducted a cross- sectional study (N = 866; 66.3% women, Mage = 27.40, SD = 8.58) with individuals in monogamous (n = 552), non-consensual non-monogamous (NCNM; n = 210) and consensually non-monogamous (CNM; n = 104) relationships. Results showed that CNM individuals used internet pornography substantially more than the other two groups, but they were as sexually satis- fied with themselves and with their primary partner as monogamous individuals. NCNM individuals were the least sexually satisfied and reported more sexual arousal difficulties than the other groups. Results further showed that CNM individuals included their primary partner in their internet pornography use more frequently than the other groups, and this inclusion was positively associated with sexual satisfaction with the primary partner. The frequency of internet pornography use with the partner was negatively associated with sexual arousal difficulties for monogamous individuals and positively associated with personal and relational sexual satisfaction in both monogamous and NCNM individuals. These results complement past findings by shedding light on the role of internet pornography use for different relationship agreements, and its association with personal and relational experiences.